Occurrence of Dental Caries among the Adults Attending a Regional Referral Hospital in Tanzania - Singh, Sohal Karpal; Stanslaus, Owibingire Sira; Aroon, 3Hirani Vanisha (Journal of Orofacial Research, 2014)
Background: Dental caries remain the main oral disease with greatest socioeconomic impact that correlates with lifestyle  specifically dietary patterns and oral hygiene practices. Being a cumulative process, the numbers of individuals affected increase with age. This study aimed at determining the occurrence of dental caries among adult patients attending a public regional hospital. Materials and methods: A cross-sectional studies involving 436 adult patients who attended at Musoma Referral Hospital for dental care. Patients were systematically examined for dental caries, which were scored as per WHO criteria. Results: Among 436 patients 256 (58.7%) were female, with  male to female ratio of 1: 1.42. The mean age was 36.9 ± 15.61 years with range of 18 to 91 years. One or more carious tooth was observed in 87.8%, the 18 to 29 years was the age group most affected. The mean decayed, missing, filled teeth (DMFT) was 4.67 ± 0.19 whereby the D (decayed) component had the highest proportion 3.01 ± 0.12, and F (filled) component the lowest 0.1 ± 0.03. On average the M (missing) teeth was 1.57 ± 0.12. When compared within the gender the mean D component was significantly higher among female (p < 0.05). Conclusion: The caries observed occur more in females and in younger age group. The observed DMFT is much higher than population average since this is a cohort of patients seeking care. There is high D component and very low F component of  DMFT mainly due to lack, and to some extent low utilization of restorative dental services.